1988
DOI: 10.1007/bf01962340
|View full text |Cite
|
Sign up to set email alerts
|

Value of cerebrospinal fluid analysis in the differential diagnosis of meningitis: A study in 710 patients with suspected central nervous system infection

Abstract: A prospective study to determine the value of cerebrospinal fluid analysis in the differential diagnosis of meningitis was performed in 710 consecutively observed patients, both children and adults, who underwent lumbar puncture due to suspected central nervous system infection. Diagnoses included acute or presumed bacterial meningitis (n = 79), acute or presumed viral meningoencephalitis (n = 218), acute unclassified meningitis (n = 6), other infections of the central nervous system (n = 37), non-infectious n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 47 publications
2
47
2
Order By: Relevance
“…However, high specificity is desired to exclude expensive treatment of false positive cases (8). Previous studies have shown CSF lactate to have the highest sensitivity (89%-100%) and specificity (96%-100%) for discriminating acute untreated bacterial meningitis from viral meningitis, when the threshold limit was set at 3.5 mmol/L (36,37). This limit proved to also be relevant for tuberculosis (38), Listeria monocytogenes (39) and fungal meningitis (40).…”
Section: Figure 1 Csf Lactic Acid (Mmol/l) Concentration In the Studimentioning
confidence: 99%
See 2 more Smart Citations
“…However, high specificity is desired to exclude expensive treatment of false positive cases (8). Previous studies have shown CSF lactate to have the highest sensitivity (89%-100%) and specificity (96%-100%) for discriminating acute untreated bacterial meningitis from viral meningitis, when the threshold limit was set at 3.5 mmol/L (36,37). This limit proved to also be relevant for tuberculosis (38), Listeria monocytogenes (39) and fungal meningitis (40).…”
Section: Figure 1 Csf Lactic Acid (Mmol/l) Concentration In the Studimentioning
confidence: 99%
“…CSF glucose is considered by clinicians to be a good marker to discriminate acute bacterial meningitis from viral meningitis. However, some authors reported low-sensitivity (around 50%) and high specificity with CSF glucose (36,37,41). Because CSF glucose concentrations are dependent on blood glucose concentrations, blood must be collected at the same time as CSF.…”
Section: Figure 1 Csf Lactic Acid (Mmol/l) Concentration In the Studimentioning
confidence: 99%
See 1 more Smart Citation
“…6 To optimise effective use of CSF PCR assays, previous studies have suggested algorithms based on CSF leucocyte count and total protein levels to determine when CSF PCR assays are indicated, 7,9 both of which are predictive of CNS infections. 3,8,9 In order to evaluate the appropriateness of CSF PCR requests at the James Cook University Hospital on the basis of criteria recommended in one of these studies, 7 a retrospective audit of all CSF PCR tests requested over a two-year period was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] However, neither finding is diagnostic, and retrospective data suggest that CSF glucose and protein levels add little to initial treatment or disposition determinations. [8][9][10][11][12][13][14][15] Previous studies primarily included adults and were retrospective. We concurrently evaluated whether pediatric emergency physicians (EPs) consider either CSF glucose or protein values in making decisions to initiate antibiotic treatment and/or admit to the hospital patients undergoing lumbar puncture.…”
mentioning
confidence: 99%